How do judgmental overconfidence and overoptimism shape innovative activity? - Holger Herz; Daniel Schunk; Christian Zehnder (Center for Economic Studies and ifo Institute (CESifo), 2013)
Recent field evidence suggests a positive link between overconfidence and innovative activities. In this paper we argue that the connection between overconfidence and innovation is more complex than the previous literature suggests. In particular, we show theoretically and experimentally that different forms of overconfidence may have opposing effects on innovative activity. While overoptimism leads to an innovation enhancing effect, judgmental overconfidence inhibits innovation. Our results indicate that future research is well advised to take into account that the relationship between innovation and overconfidence may crucially depend on what type of overconfidence is most prevalent in a particular context.
Keywords: C92; D83; D23; 330; innovation; entrepreneurship; overconfidence; experiment; Innovation; Unternehmer; Persönlichkeitspsychologie; Selbstevaluation; Test